Diesel Engine Emission Reduction Using Catalytic Nanoparticles: An Experimental Investigation. (25th February 2013) - Sajeevan, Ajin C.; Sajith, V.
Abstract : Cerium oxide being a rare earth metal with dual valance state existence has exceptional catalytic activity due to its oxygen buffering capability, especially in the nanosized form. Hence when used as an additive in the diesel fuel it leads to simultaneous reduction and oxidation of nitrogen dioxide and hydrocarbon emissions, respectively, from diesel engine. The present work investigates the effect of cerium oxide nanoparticles on performance and emissions of diesel engine. Cerium oxide nanoparticles were synthesized by chemical method and techniques such as TEM, EDS, and XRD have been used for the characterization. Cerium oxide was mixed in diesel by means of standard ultrasonic shaker to obtain stable suspension, in a two-step process. The influence of nanoparticles on various physicochemical properties of diesel fuel has also been investigated through extensive experimentation by means of ASTM standard testing methods. Load test was done in the diesel engine to investigate the effect of nanoparticles on the efficiency and the emissions from the engine. Comparisons of fuel properties with and without additives are also presented.